2018
DOI: 10.1111/ajsp.12321
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of cultural diversity: Psychological consequences of different patterns of intercultural contact and mixing

Abstract: Culture mixing is a critical consequence of globalization. Thus, predicting the effects of globalization on individual psychological processes requires understanding the effects of exposure to culture mixing on cognition, attitudes, and behaviors. Prior research has demonstrated that perceiving the mixing of own and foreign cultures can trigger subsequent shifts across a wide range of psychological processes. This article proposes that the psychological consequences of culture mixing can be understood through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 108 publications
(128 reference statements)
1
23
0
Order By: Relevance
“…Globalization, widespread use of information and communication technology, and the exercise of “soft power” by nations such as the United States and China have produced increased opportunities for elements of diverse cultures to mix and influence one another. Yet, intercultural contact and mixing may take on diverse patterns or forms, some of which may be more accepted or tolerated than others (Cheon, 2019; Hong & Cheon, 2017). To address this pressing issue, this study examined how much people would tolerate mixing of images of one’s own culture with those of a foreign culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globalization, widespread use of information and communication technology, and the exercise of “soft power” by nations such as the United States and China have produced increased opportunities for elements of diverse cultures to mix and influence one another. Yet, intercultural contact and mixing may take on diverse patterns or forms, some of which may be more accepted or tolerated than others (Cheon, 2019; Hong & Cheon, 2017). To address this pressing issue, this study examined how much people would tolerate mixing of images of one’s own culture with those of a foreign culture.…”
Section: Introductionmentioning
confidence: 99%
“…Culture fusion is one manifestation of culture mixing, which involves the direct blending of elements of a foreign culture into a representation of one’s own local or heritage culture to produce a hybrid cultural representation (Hao et al, 2016). Prior research has suggested that compared with other patterns of culture mixing, culture fusion may be perceived as especially intrusive and a threat to the purity or integrity of local cultures, given its ability to transform cultural markers (e.g., icons, symbols, practices) of shared in-group identity to also embody cultural identity markers of foreign out-groups (Cheon, 2019). Consequently, culture fusion may be more likely to be rejected than other, less transformative, manifestations of cultural diversity, such as multiculturalism, in which diverse cultural representations and practices co-exist but as distinct entities without direct mixing.…”
Section: Introductionmentioning
confidence: 99%
“…The protective nature of cultural icons against threat emphasizes the importance of having identifiable symbols and the association of experiences within a cultural group to those symbols. Recent research in responses to perceived mixing of cultures have indeed suggested that people who are highly identified with their cultures may find mixing of foreign influences with symbols and representations of their own cultures especially aversive and distasteful (Cheon et al, 2016; Cheon, 2018). More narrow cultural groups also represent themselves with having clear and strong symbols.…”
Section: Discussion: Concepts Models and Computational Culture Neuromentioning
confidence: 99%
“…Review papers—whether theoretical, methodological, or both—are likely to provide readers of the journal powerful guides for understanding significant movements in theory and empirical research. In recent volumes of AJSP , we have published review papers that provide new and broad theoretical frames for understanding research on particular topics (e.g., Cheon, ; Hamamura, ) or that consider evidence on different positions regarding a theoretical point (e.g., Caprara et al., ; Takano & Osaka, ). We encourage authors to submit their best review papers, and we are particularly interested in review papers that incorporate theoretical perspectives and data published in Asian domestic journals that are not easily accessible from other parts of the world.…”
Section: Aims and Scopementioning
confidence: 99%